PDC Bit Hydraulic & Mud Rheological simulation to model pressure drop across Bit - Kai Sheng, O. (EDP Sciences, 2017)
During fluid flow from larger to smaller diameter pipes, a drop in pressure is experienced. High pressure drop across bit indicated high energy loss in the hydraulic system and also a setback to ROP performance. This is inefficient and pressure pumps would have to be of bigger sizing to make up for the losses. Present form of pressure drop models is in terms of mud density, flow rate, and total flow area. The objective of this paper is focused on the analysis of CFD simulation and to propose optimized parameters for improved ROP. Single phase flow study of Yield Power Law mud rheology was simulated at bottom hole of horizontal section. Parametric study on mud rheology was carried using DOE. Design points of DOE were sampled mostly using Latin Hypercube Sampling and a few by Central Composite Design. It is found that Kriging Response Surface method generated the best regression model where the predicted values are closest to the observed values and has the lowest Maximum Relative Residual (0.000336). Inlet velocity and Power Index have significant effect on pressure drop. Consistency Index showed moderate effect while Yield Stress showed small effect to pressure drop. This research has proven that pressure loss model should take into account of mud rheology. Further research can be done with PDC bit rotation and its effect on mud behaviour. © The authors, published by EDP Sciences, 2017.